2012
DOI: 10.1002/nau.22222
|View full text |Cite
|
Sign up to set email alerts
|

Can we identify men who will have complications from benign prostatic obstruction (BPO)?: ICI‐RS 2011

Abstract: In contrast to the widespread belief of urologist, there is only rudimentary data available showing no convincing association between urinary tract complications and BPO. The ICI-RS proposes that prospective trials are conducted to demonstrate the association between complications and BPO by using cystometry, pressure-flow (P/F) studies, and other commonly used BPO parameters in men with complications and comparing those with a cohort of age-matched men without complications. Non-invasive proxy parameters of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 44 publications
0
33
0
1
Order By: Relevance
“…Hydronephrosis, renal insufficiency, and urinary retention appear with greater prevalence in patients with symptoms or signs of BPO [57]. Even though BPO may be partly responsible for these complications, there is no conclusive evidence that BPO is the primary cause [57].…”
Section: Renal Function Measurementmentioning
confidence: 99%
“…Hydronephrosis, renal insufficiency, and urinary retention appear with greater prevalence in patients with symptoms or signs of BPO [57]. Even though BPO may be partly responsible for these complications, there is no conclusive evidence that BPO is the primary cause [57].…”
Section: Renal Function Measurementmentioning
confidence: 99%
“…This increased nerve activity may contribute to increased prostate smooth muscle tone and subsequent bladder outlet obstruction. Increased outlet resistance can lead to obstructive symptoms as well as potential future irritative symptoms [12]. In addition, increased insulin concentrations secondary to diabetes may have a trophic affect that leads to enlarged prostate size [13].…”
Section: Hypothesized Mechanismsmentioning
confidence: 99%
“…A key goal of treatment for BPH with LUTS is to prevent urinary retention and the need for prostate surgery [ 17 ]. Urinary retention can have a significant impact on patient quality of life, and the effectiveness of drug therapy following prostate surgery to treat urinary tract syndrome is less than ideal [ 18 ]. These two results are often used as indicators for the clinical evaluation of BPH with LUTS.…”
Section: Discussionmentioning
confidence: 99%
“…Third, this study found that for patients with a maximum urinary flow rate of 15ml/sec, patient age and residence in southern and eastern Taiwan are all risk factors for urinary retention and prostate surgery. Patient age is already a widely recognized risk factor [ 18 ]. However, patients residing in southern and eastern Taiwan are at greater risk for urinary retention and prostate surgery than those living in the north and west.…”
Section: Discussionmentioning
confidence: 99%